Comparative Study of Air Pollutant Levels in Smoke-Free Areas and Active Smoking Areas - Indasah; Gede Ivan; Abdul Kohar (Universitas STRADA Indonesia, 2023)
Background: The increasing prevalence of smoking in public spaces has raised significant concerns regarding air quality and public health. As urbanisation continues to expand and populations grow, the visibility of smoking in public areas, including parks, streets, and outdoor dining venues, has become more pronounced. This trend not only poses immediate discomfort for non-smokers but also raises broader implications for community health and environmental quality. Purpose: This study aimed to compare air pollutant levels in smoke-free areas versus active smoking areas, focusing on particulate matter (PM2.5 and PM10), carbon monoxide (CO), and volatile organic compounds (VOCs). Method: Employing a quantitative research design, air quality samples were collected from various locations over a six-month period. Results: The findings revealed that active smoking areas exhibited significantly higher levels of pollutants compared to smoke-free zones, with PM2.5 concentrations exceeding safe limits by over 150% in some instances. Conclusion: This study underscores the urgent need for stricter enforcement of smoking regulations to safeguard public health and enhance environmental quality.